2008
DOI: 10.1037/0033-295x.115.1.101
|View full text |Cite
|
Sign up to set email alerts
|

Threaded cognition: An integrated theory of concurrent multitasking.

Abstract: The authors propose the idea of threaded cognition, an integrated theory of concurrent multitasking--that is, performing 2 or more tasks at once. Threaded cognition posits that streams of thought can be represented as threads of processing coordinated by a serial procedural resource and executed across other available resources (e.g., perceptual and motor resources). The theory specifies a parsimonious mechanism that allows for concurrent execution, resource acquisition, and resolution of resource conflicts, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
497
1
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 527 publications
(515 citation statements)
references
References 83 publications
(163 reference statements)
16
497
1
1
Order By: Relevance
“…A further improvement is achieved by a reduction of the use of declarative resources, which occurs for example when instructions for actions have to be retrieved from memory. As shown by Salvucci and Taatgen [3], a visual dialling task produced a higher level of interference with driving than did a comparable voicedialling task. Similarly, a study by Levy et al [20] showed that resource interference degrades performance.…”
Section: Spoken Language Interfaces In Drivingmentioning
confidence: 99%
See 2 more Smart Citations
“…A further improvement is achieved by a reduction of the use of declarative resources, which occurs for example when instructions for actions have to be retrieved from memory. As shown by Salvucci and Taatgen [3], a visual dialling task produced a higher level of interference with driving than did a comparable voicedialling task. Similarly, a study by Levy et al [20] showed that resource interference degrades performance.…”
Section: Spoken Language Interfaces In Drivingmentioning
confidence: 99%
“…In order to make predictions about how different interface solutions affect the driving task, we lean on the concepts provided by the theory of threaded cognition [3]. In this theory it is assumed that different tasks within a multitasking environment are made up of different threads.…”
Section: Spoken Language Interfaces In Drivingmentioning
confidence: 99%
See 1 more Smart Citation
“…This is clarified in the theory of threaded cognition [18], which describes each activity a person is performing as a cognitive thread. Multiple threads can be active at the same time, for example, we can easily drive a car (thread one) and listen to the radio (thread two) at the same time, as also evident from multiple resource theory [19].…”
Section: Divided Attention and Multitasking Theorymentioning
confidence: 99%
“…The task was to read a note on a music score, and play it on the piano. The model did not intend to capture looking ahead behaviour (Fourie, 2004), the representation and processing of musical sounds (Chikhaoui, Pigot, Beaudoin, Pratte, Bellefeuille & Laudares, 2009), learning motor skills (Jabusch, Alpers, Kopiez, Vauth & Altenmüller, 2009), movement preparation (Palmer, 2005), and multitasking of music reading and motor movements as threaded cognitive tasks (Salvucci & Taatgen, 2008) were excluded from the models.…”
Section: Introductionmentioning
confidence: 99%